Thyroid storm after chest trauma - Novaković Tatjana; Dejanović Bogdan; Vitošević Zdravko; Milošević Nenad; Milošević Jovana; Jovićević Ljiljana; Novaković Emilija; Mirković Miloš V.; Mirković Zlatica (Praxis Medica, 2020)
Thyroid storm is an acute and severe complication of thyrotoxicosis. It is characterized by high fever, sweating, tachycardia, and often heart failure too. The objectives of the paper is to present the case of a patient with thyroid storm developed after the trauma of the chest at previously apparently healthy individuals, diagnosed on the basis of clinical preview and based on the diagnostic criteria according to Burch and Wartofsky. The most common complication is Mb. Graves - Basedow, but often associated with multi-nodose goiter. Thyroid storm is the most severe form of thyrotoxicosis with a mortality rate of 8 to 25 %. Case report. We present an interesting case from our practice: thyroid storm caused after chest trauma in apparently healthy people, but with unrecognized hyperthyroidism and thyroid gland nodule. Conclusion. The objectives of this presentation were to raise awareness of the association between signs and symptoms of thyroid storm that dominate the clinical picture and complicate the initial presentation and the evolution of the situation caused by trauma. The treatment of hyperthyroidism resulted in conversion in sinus rhythm, withdrawal of symptoms and signs heart failure, and normalization of artery pressure.